Floorplan for a house at Castlecrag for Mr Lee, New South Wales, ca. 1920 - Griffin, Walter Burley, 1876-1937 (ca. 1920.)
"The plan was drawn up for Mr Lee, however the family decided to move to Manly, hence the house at Castlecrag was never built"--Information supplied by Mrs Simpson-Lee.
Title devised by cataloguer based on information from acquisitions documentation.
Inscriptions: "M.Lee residence W.B.Griffin architect, Castlecrag, Willoughby"--Upper left corner.
Condition: Tears, creases, spotting and yellowing.
Also available online
Donated by Mrs Moya Simpson-Lee, 2010.
Keywords: Architecture, Domestic -- New South Wales -- Castlecrag -- Designs and plans; Architectural drawing -- New South Wales -- Castlecrag; Blueprinting; Castlecrag (N.S.W.) -- Buildings, structures, etc. -- Pictorial works